2018
DOI: 10.1177/1129729818761278
|View full text |Cite
|
Sign up to set email alerts
|

Use of 8-cm 22G-long peripheral cannulas in pediatric patients

Abstract: Long peripheral cannulas represent a valid option for medium-term intravenous access in children undergoing surgery. Majority of patients will be successfully treated with one long peripheral cannula for the duration of their treatment without the need for further cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…For hospitalized children and adolescents, PIVCs and midline catheters were reported as appropriate for short-term peripherally compatible therapies in multiple studies because of their low risk of catheter-related infections and thrombosis in comparison to PICCs. 14,43,94,100,127,143 However, in one study, the authors suggested that these devices are associated with increased risk of occlusion with extended dwell times. 127 PICCs were reported to have high insertion success rates 84 and low failure rates in children and adolescents, 6,59 although one study reported severe complications in 40.1% of failed PICCs, associated with increasing patient age.…”
Section: Figurementioning
confidence: 99%
“…For hospitalized children and adolescents, PIVCs and midline catheters were reported as appropriate for short-term peripherally compatible therapies in multiple studies because of their low risk of catheter-related infections and thrombosis in comparison to PICCs. 14,43,94,100,127,143 However, in one study, the authors suggested that these devices are associated with increased risk of occlusion with extended dwell times. 127 PICCs were reported to have high insertion success rates 84 and low failure rates in children and adolescents, 6,59 although one study reported severe complications in 40.1% of failed PICCs, associated with increasing patient age.…”
Section: Figurementioning
confidence: 99%
“…Although currently underutilised, this seems promising access for children undergoing surgery, where a single venous cannula can suffice the duration of care. [21]…”
Section: Types Of Vascular Accessmentioning
confidence: 99%
“…LPCs are less durable than MCs and, thus, may only remain in situ for 4 weeks. 7 An important difference between MCs and LPCs is their method of insertion. [8][9][10] LPCs are inserted with a simple catheter-over-needle technique or a direct Seldinger technique (originally developed for arterial catheterisation).…”
mentioning
confidence: 99%
“…Among which, we identified over a dozen different labels. These include '15 cm catheter', 12 'catheter inserted with a Seldinger method', 13 'extended dwell/midline peripheral catheter', 14 'Leaderflex line', 15 'long catheter', [16][17][18] 'long IV catheter', 18 'long peripheral cannula', 7,9 'long peripheral catheter', 10 'long peripheral venous catheter', 8 'long polyurethane catheter', 10 'midline cannula', 16 'mini-midline', 19 'peripheral intravenous catheter', 20 'Seldinger catheter', 18 'short midline catheter', 10 'short long line', 15 and 'ultrasound-guided peripheral intravenous catheter'. 1,13 Further details are presented in Table 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation